Radzieckie organy Bezpieczeństwa Państwowego na Ukrainie:czerwiec–grudzień 1941 roku. Zarys problematyki - Баран, Володимир Кіндратович; Baran, Volodymyr K. (lnstytutu pamięci narodoweј, 2017)
У статті на основі розсекречених архівних документів проаналізовано діяльність радянських органів державної безпеки в Україні у червні-грудні 1941 року.

The article presents the outline of the activities undertaken by the Soviet state security services in Ukraine between June and December 1941. The author analyses different aspects of the operation of Soviet security services in the initial period of the German- -Soviet war, in particular: the first organizational initiatives taken by the KGB USSR, the control of correspondence and public moods, the observation of refugees and establishment of evacuation points, the struggle against the enemy’s parachute operations and establishment of deadly battalions, the deportation of prisoners to the east of the country and executions in prisons in the western oblasts of the USSR, the fight against desertion and spreading panic at the rear, repression against the so-called anti-soviet and suspicious element, the mass deportations of citizens on ethnic grounds, the creation of subversive and reconnaissance groups as well as merging underground and guerrilla movements in the occupied territories. Several characteristic documents from the archives of the Soviet state security services are annexed to this article.
Soviet security services in Ukraine: June–December 1941. Outline of the issues
Keywords: органи державної безпеки; репресивна політика; партизанський рух; німецько-радянська війна; депортація населення; organs of state security; repressive politics; partizvnskiy motion; german-soviet war; deportation of citizens